CO2 capture-driven thermal battery using functionalized solvents for plus energy building application. (15th May 2022) - Kim, Seonggon; Lee, Jae Won; Choi, Hyung Won; Lee, Geun Jeong; Xu, Ronghuan; Yoon, Seok Ho; Xu, Zhenyuan; Wang, Ruzhu; Tae Kang, Yong
Graphical abstract: Highlights: Amine-functionalized solvents are developed for thermal battery application. Thermal energy storage density reaches 2.187 kJ/g. Energy storage density of thermal battery is 0.57 kJ/g. Coefficient of performance of thermal battery is 0.66. Thermal energy can be saved by 477.9 MJ/m 2 for the building application. Abstract: Renewable energy has the drawback of intermittent power generation, and it should be linked to an energy storage system. However, the efficiency and density of the conventional thermal energy storage technologies are low. Herein, for building applications, CO2 capture-driven thermal battery has been developed using solvents composed of amine-functionalized mesoporous silica (3-APTES-SBA-15) and an amine absorbent (MEA). The thermal energy is discharged through the exothermic reaction of amine-CO. When the renewable energy is supplied to the battery, amine-CO2 bonds are broken, which corresponds to charging process. 3-APTES-SBA-15/MEA presents a superior energy storage density of 2.187 kJ/g and an efficiency of 91.5%. It is sufficient for producing heating/hot water considering the discharging temperature, and there is no loss even if stored for a long time. The thermal battery system presents a coefficient of performance of 0.66 and a thermal energy storage density of 0.57 kJ/g. When the thermal battery is combined with solar thermal energy harvesting system, the thermal and electric energy consumptions are reduced by 22.0% (477.9 MJ/m 2 ) and 19.6% (156.9 MJ/m 2 ), respectively. The CO2 capture-driven thermal battery will contribute to manage renewable energy and reduce grid energy consumption for building applications.